The Effect of Popular English Song and English Movie on Students’ Pronunciation at MTsN 3 Jakarta - Khoiriyah Shofiyah Tanjung (Asosiasi Dosen Perguruan Tinggi Islam, 2016)
This research aims to discover whether the English popular songs and movies are an effective media in enhancing and improving students' pronunciation. The subjects in the study were involving 62 students from grade 8 in MTsN 3 Jakarta and were divided into 2 groups. 31 students from class 8-2 involved in movie class while 31 students in class 8-3 have English songs popular class.The data are taken from the study of the accuracy of the student in pronouncing the words in a simple text at the beginning and end of the test in each experimental class. During the students read the text, the researcher recorded their voice to be analyzed for the pronunciation.In this research, it was found that students who have popular English songs and English movie in their class show progress in pronunciation. It was proved by the scores that they got when the post test after training, higher than pre tests before training. This suggests that both media are